Обломов: [роман : 16+] / Иван Гончаров - Гончаров Иван Александрович (Pocket book, 2016)
Экземпляры: С/а ДБ (20191014) / Инвентарный номер: 110856 / Цена: 80.00 / Авт.знак: Г 65 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)1